Design of a low bit rate STDM multiplexing - Shah, Asadullah; Abdullah Zammarh, Nuha (IIUM Press, 2011)
A low bit rate STDM multiplexer architecture design for thing route channels is provided in this chapter. A thin route communication channel is able to transmit 64Kbps to 128Kbps. Allowing compressed speech using STDM maximize the bandwidth by allowing more users than the capacity ofthe channel. The design provided in this chapter is based upon, compressed speech as 6.4Kbps, packet discarding from the sources in case of overload and packet reconstruction to mitigate the effects ofthe lost (dropped) packets